Simulação de transporte eletrônico em dispositivos unimoleculares baseados em indicadores de pH - GRANHEN, Ewerton Ramos (Universidade Federal do Pará, 2013)
In recent decades, several researchers have tried employ molecules in electronic devices of nanoscale. For this reason, different electro / optical parameters, governing the electronic transport in organic molecules, need to be analyzed. In this work was developed a charge transport study to the composed propyl red, popularly used as pH indicator. The motivation to study it results from its structure formed of donor-acceptor subunits, coupled via azo group (N = N), a well known feature in molecular rectifiers. The methodology used to treat the system in equilibrium is based on Molecular Mechanics and Hartree-Fock methods. However, another method, based on the Landauer-Büttiker formalism, to non-equilibrium system was employed. Through these methods, the feature curves of molecular system were drawn and compared. The result of comparison lowed explain the phenomena that govern the electronic transport in nanostructure. Besides that, was analyzed the effects of metal contacts, connected on molecules in presence of external electric field.